Алелопатична функція фенольних сполук плодових рослин - Moroz, P.A.; Osipova, I.Y.; Derevyanko, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
The data about the contents of phenolic compounds in fruit trees falls and roots (Rosaceae Juss.) is set out. It was determined that phenolic compounds are the reason of allelopathic postaction of fruit trees in orchards.